ANALISIS CAMPUR KODE PADA SISWA KELAS XI SMK NEGERI 1 CIMAHI DALAM MENCERITAKAN KEMBALI CERPEN - Rizki Dewi Oktavia; Lina Marlina; Restu Bias Primandhika (IKIP Siliwangi, 2019)
This research is conducted due to the problems found in research field. The problems found in this research are the existence of code-mixing used by the 11th grade students of SMKN 1 Cimahi when they were asked to retell a short story. Code-mixing happens when language speakers mix traditional language with Indonesian language at once. In other words, a person who speaks in main Indonesian language has the autonomous function. While the traditional language, is only an auxiliary tool that has no autonomous function. The method used in this research is a descriptive qualitative research. Observation and questionnaire are implemented as the instruments of this research. The population of this research is all of 11th- grade-student of SMKN 1 Cimahi and the sample contains 25 students of 11 IOP A class. The questionnaire was conducted to 25 students, but the observation was only conducted to 5 students. This research found that students often use traditional language when they speak in Indonesian language. Unconsciously, students frequently use kecap penganteb when they speaking.